Assessment of Incidence of Phlebitis Associated with Peripheric Intravenous Catheter and Affecting Factors - Soner Beşe; Betül Tosun; Nuran Tosun (Dokuz Eylul University, 2020)
Background: Peripheral venous catheters which are vital tools when applied correctly and effectively, can cause phlebitis due to many factors. Objectives: To assess the incidence of phlebitis associated with peripheric intravenous catheter and affecting factors in an internal medicine clinic. Methods: This descriptive, cross-sectional study was conducted in December 2018-March 2019 in the internal medicine clinic. The sample consisted of 195 peripheric intravenous catheters on 93 patients. Data was collected by "Patient Information Form" and "Phlebitis Diagnosis Scale". Chi-square test was used to analyze discrete variable and risk factors were determined by using Logistic Regression analyses. Results: Mean age of the participants was 56.86 ± 18.031 years and 50.5% of them were male. According to the Phlebitis Diagnosis Scale, phlebitis symptoms were observed in 28.2% (n = 55) of the 195 peripheric catheters. Phlebitis incidence was higher in patients aged 66-90 years old (p = .015), patients who had chronic diseases (p = .005), patients who had continuous intravenous infusion (p = .007), patients who were catheterized for 72-96 hours (p = .045), catheters placed on the inactive upper extremity of the patient (p = .012), catheters which were not placed successfully in the first attempt (p = .001), catheters which were placed on a vein which was previously catheterized (p = .001). Conclusion: Phlebitis symptoms were seen in more than one quarter of the patients. Phlebitis incidence was increased in elderly patients with chronic diseases and patients having continuous intravenous infusion, repetitive catheterization in the same vein and prolonged catheterization time. It is recommended for nurses to keep in mind the risk factors for phlebitis development during catheter application and care and to assess the patients with peripheric intravenous catheter regularly with valid and reliable tools and to conduct studies on minimizing the phlebitis development risk.